2014
DOI: 10.1107/s2053230x1401557x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of nucleoside diphosphate kinase from pacific shrimp (Litopenaeus vannamei) in binary complexes with purine and pyrimidine nucleoside diphosphates

Abstract: Nucleoside diphosphate kinase (NDK; EC 2.7.4.6) is an enzyme that catalyzes the third phosphorylation of nucleoside diphosphates, leading to nucleoside triphosphates for DNA replication. Expression of the NDK from Litopenaeus vannamei (LvNDK) is known to be regulated under viral infection. Also, as determined by isothermal titration calorimetry, LvNDK binds both purine and pyrimidine deoxynucleoside diphosphates with high binding affinity for dGDP and dADP and with no heat of binding interaction for dCDP [Quin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In the Pp AK-Arg structure we found that Glu225 is positioned in a similar way, making only one salt-bridge with NH 2 (ω)-1 of the arginine guanidino group end. This small local conformational change was also observed in Lv AK-Arg structure and it is postulated to lead to a productive active site in the closed conformation ( López-Zavala et al, 2014 ; Zhou et al, 1998 ).…”
Section: Discussionsupporting
confidence: 52%
“…In the Pp AK-Arg structure we found that Glu225 is positioned in a similar way, making only one salt-bridge with NH 2 (ω)-1 of the arginine guanidino group end. This small local conformational change was also observed in Lv AK-Arg structure and it is postulated to lead to a productive active site in the closed conformation ( López-Zavala et al, 2014 ; Zhou et al, 1998 ).…”
Section: Discussionsupporting
confidence: 52%
“…Noticeably, drug metabolism might be hindered due to the significantly downregulation of a kinase gene. The kinase (EC 2.7.4.6) is a nucleoside-diphosphate kinase, catalyzing phosphorylation of nucleoside diphosphates to nucleoside triphosphates for DNA replication [ 46 ]. Understanding why these genes were downregulated in oxamyl-treated TPBs cannot be ignored in further studies.…”
Section: Resultsmentioning
confidence: 99%